2019
DOI: 10.1186/s12889-019-6793-2
|View full text |Cite
|
Sign up to set email alerts
|

Mediated representations of violence against women in the mainstream news in Australia

Abstract: Background How the mainstream news media report violence against women is significant if levels of violence are to be reduced and ultimately eliminated. Media reporting is an important indicator through which to measure progress towards shifting social and cultural norms that reinforce or challenge the place of violence against women in our society. The current study, therefore, aimed to establish a baseline picture of the extent and nature of reporting of violence against women by the mainstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 25 publications
2
51
1
Order By: Relevance
“…As a result of the investigation made, it can be said that this result complies with the literature (22). Unlike our result, studies reporting that news about external sources are made more were found as well (30,33). When the news contents are reviewed, it is seen that there are news on physical matters and/or problems such as "pregnancy and breastfeeding period changes" (22.5%), description/ introduction such as "introduction of a product used in breastfeeding period etc."…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…As a result of the investigation made, it can be said that this result complies with the literature (22). Unlike our result, studies reporting that news about external sources are made more were found as well (30,33). When the news contents are reviewed, it is seen that there are news on physical matters and/or problems such as "pregnancy and breastfeeding period changes" (22.5%), description/ introduction such as "introduction of a product used in breastfeeding period etc."…”
Section: Discussioncontrasting
confidence: 91%
“…In the research, it was found that the position of news on midwifery and fertility is mostly on the other part (top, middle and bottom part) (88.9%) (Table 3). In literature review, it was found in a study reviewing news on women that the news are quite few on the headline and subheading (21)(22)(23)30) and health related news are mostly published on other parts of the newspaper (22) similar to our results.…”
Section: Discussionsupporting
confidence: 85%
“…An analysis of 444 Australian media reports about violence against women showed a similar result. For example, over 95% of reports excluded information on victim or perpetrator services (e.g., helplines, advocacy, or counseling services) [ 55 ]. One possible explanation for this finding is that Chinese journalists may not have requisite knowledge and awareness to incorporate appropriate information in their stories.…”
Section: Discussionmentioning
confidence: 99%
“…This is not to suggest that news media audiences digest reporting in a simplistic and uncontested way; readers may challenge and disrupt news media discourse, or interpret reporting in vastly different ways (Harrington, 2018). Nonetheless, media reporting is a key site of discourse on GBV and plays a central role in shaping how this issue is articulated and understood, and in driving primary prevention efforts, policy and other responses (Sutherland et al, 2017;Sutherland et al, 2019).…”
Section: Media Reporting On Gbvmentioning
confidence: 99%
“…Breen et al's (2017) analysis of a high-profile Australian rape trial, for example, found that news media reporting emphasised the negative impact the guilty finding would have on the perpetrator's future prospects and his persistent claim that the encounter was a consensual one (see also Smith et al, 2019). In contrast, the survivor's voice was less commonly quoted, and quotes used from her victim impact statement "served to discursively minimise her experience" (Breen et al, 2017, p.248;see also O'Hara, 2012;Sutherland et al, 2019). In other cases, the actions and responsibility of the perpetrator are obscured through the use of passive voice, with GBV becoming something that just happens to women (Easteal et al, 2019).…”
Section: Media Reporting On Gbvmentioning
confidence: 99%